PENGARUH METODE SOLMISASI PADA LAGU “BURUNG KAKAK TUA” MELALUI MEDIA ANGKLUNG TERHADAP KEMAMPUAN DAYA INGAT ANAK USIA 5-6 TAHUN: Penelitian Eksperimen pada Anak Usia Dini - Irma Sholikhah; Nurhenti Dorlina Simatupang; Sri Widayati; Yes Matheos Lasarus Malaikosa (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
Memory ability is an important aspect in the cognitive development of early childhood because it plays a role in the process of storing, processing, and recalling information received. However, the results of initial observations at DWP Jono Kindergarten showed that some children in group B still had difficulty remembering the sequence of notes, song lyrics, and the sound of the angklung during singing activities. The angklung musical instrument available at school has not been utilized as a learning tool, so children have not gained musical experience that can support memory strengthening. This study aims to analyze the effect of the solmization method on the song "Burung Kakak Tua" through the angklung musical instrument on the memory ability of children aged 5-6 years. This study used a quasi-experimental approach with a non-equivalent control group design involving 11 children in the experimental group and 22 children in the control group. Data were collected through pretest, treatment, and posttest, then analyzed using the Wilcoxon Signed Rank Test because the data is non-parametric. The results of the analysis showed a significance value of 0.008 <0.05, so H₀ was rejected and H₁ was accepted. This indicates a significant difference between pretest and posttest scores. Thus, the solmization method using the angklung musical instrument has been shown to significantly improve children's memory.